The Effect of Security and Privacy Perceptions on Customers’ Trust to Accept Internet Banking Services: An Extension of TAM - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Abu-Shanab, Emad; Elayah, Nabil (Medwell Journals, 2016)
This study attempts to answer the main research question: ‘Do security and privacy perceptions affect customers' trust to accept and use Internet banking technology to perform their banking transactions?’ This study examined the factors that affected Jordanian customers’ trust to accept Internet banking services. Path analysis was used to analyze 198 responses, where results suggested that the hypothesized model was an accurate reflection of the factors that affect trust to accept and use Internet banking services. Results indicated that trust has a positive effect on behavioral intention to use Internet banking services as its usefulness, security, and privacy perceptions significantly influenced the perceived trust. Finally, perceived ease of use had failed to predict Jordanians’ intention to use Internet banking.